2010
DOI: 10.1038/onc.2010.560
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-Catenin activation promotes prostate tumor progression in a mouse model

Abstract: Our previous studies have found that activation of Wnt/β-Catenin signaling resulted in mouse prostatic intraepithelial neoplasia (mPIN). In the large probasin promoter directed SV40-Large T-antigen (LPB-Tag) expressing mouse prostate, mPIN forms with rare areas of adenocarcinoma. Combining expression of both Wnt-signaling and Tag expression in the mouse prostate, we have studied the role of Wnt/β-Catenin signaling in the progression from mPIN to adenocarcinoma. Our results show that the prostates of mice expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
111
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(119 citation statements)
references
References 39 publications
8
111
0
Order By: Relevance
“…Last but not least, the activation of Wnt signals in LNCaP cells resulted in expression of neuroendocrine (NE) markers, NSE and Chr.A, signifying Wnt/ -catenin in the development of neuroendocrine differentiation (NED) . This is confirmed by in vivo studies, which have revealed areas of NED in mouse prostates expressing dominant active -catenin and T-antigen (Yu et al, 2011). While -catenin is the point of interest in terms of Wnt signaling and cancer progression, dysfunction of other components within the Wnt pathway can be equally detrimental.…”
Section: Canonical Wnt Pathway and Cap Progressionsupporting
confidence: 52%
See 1 more Smart Citation
“…Last but not least, the activation of Wnt signals in LNCaP cells resulted in expression of neuroendocrine (NE) markers, NSE and Chr.A, signifying Wnt/ -catenin in the development of neuroendocrine differentiation (NED) . This is confirmed by in vivo studies, which have revealed areas of NED in mouse prostates expressing dominant active -catenin and T-antigen (Yu et al, 2011). While -catenin is the point of interest in terms of Wnt signaling and cancer progression, dysfunction of other components within the Wnt pathway can be equally detrimental.…”
Section: Canonical Wnt Pathway and Cap Progressionsupporting
confidence: 52%
“…This suggests that aberrant expression of -catenin is likely responsible for late CaP tumorigenesis. For instance, in mouse prostate expressing SV40-large T-antigen (LPB-Tag), a powerful deactivator of p53 and retinoblastoma (Rb) family of tumor suppressors, the integration of a non-degradable -catenin gene provided additional morphological changes by transforming areas of benign HGPIN into invasive adenocarcinoma, along with an elevated expression of matrix metalloproteinase (MMP)-7 (Yu et al, 2011). MMPs are proteases known to facilitate membrane invasion by catalyzing the breakdown of the extracellular matrix (Bonfil et al, 2007).…”
Section: Canonical Wnt Pathway and Cap Progressionmentioning
confidence: 99%
“…Murine models overexpressing key components of developmental signaling pathways alone or with other genetic alterations can drive a phenotype reminiscent of late-stage prostate cancer (19)(20)(21)(22). Although these studies provide evidence of a relationship between stem-like qualities and an aggressive phenotype, no studies to our knowledge have shown a molecular relationship between aggressive prostate cancer and uncultured stem-like cells from the human prostate.…”
Section: Significancementioning
confidence: 79%
“…Synchronous activation of K-ras and b-catenin significantly reduced survival in a mouse model, associated with accelerated tumorigenesis and the development of invasive carcinoma (Pearson et al 2009). In addition, Wnt/b-catenin activation promoted PCa progression in another mouse model (Yu et al 2010), and the small molecule inhibitor of Wnt/b-catenin signaling, PKF118-310, has recently been shown to inhibit the proliferation of PCa cells (Lu et al 2009). …”
Section: Foxo3amentioning
confidence: 99%